Theological idealism of Gus Dur’s Humanitarian response towards social transformation - Gufron, M (Islah: Journal of Islamic Literature and History, 2024)
Abdurrahman Wahid is a kyai as well as an organic scholar and a divergent figure. Gus Dur believed that Islamic theology needs to be re-actualized according to current conditions. According to Gus Dur’s hermeneutical perspective on developing a theology of humanitarian action, he believed that theological writings could be understood both from ma fin nash (in the text) and ma haulan nash (around the text), with the spirit of seeking new universality of teachings.